Technological surveillance for educational innovation in the use of databases and learning management platforms at Universidad del Valle, Colombia - Cruz-Rojas, Gilbert Andrés; Molina-Blandón, Manuel Alejandro; Valdiri-Vinasco, Verónica (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article presents the results obtained in the first cycle of the Technological Surveillance project for Educational Innovation, carried out at the Universidad del Valle, based on an adaptation of the methodology proposed in the Spanish Experimental Standard UNE 166006 R + D + i Management: Technological Surveillance System. This methodological development, consisting of three phases: planning, monitoring and value construction, allowed to recognize the difficulties that teachers and students of the university have in the use of databases and learning management platforms, despite their importance as elements central to strengthen scientific production and educational quality. The results of this cycle allowed, in addition, to propose training and technological solutions that meet these needs, seeking to improve the integration of ICT and promote Educational Innovation.